Public Service Management Reform for District Regional Work Units (SKPD) in Indramayu Regency - Ismanudin; Luthfi Faisal Natsir (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This article discusses the efforts of regional governments in realizing good governance through improving the performance of sub-district government officials. Regional governments need to carry out service reform as an effort to improve things that focus more on achieving the vision, mission and goals of government organizations in accordance with the main tasks, functions and authority and strive to provide services to the community, including the District SKPD within Indramayu Regency. The results of this research show that the sub-district is a regional apparatus as a regional technical implementer which has a certain work area led by the sub-district head and has a strategic position.  Public service management reform in the District SKPD as all forms of change efforts in public (public) service management are implemented by the District Government to the community in the form of providing government administration services, either with payment or without payment to meet community needs or interests. One type of public service that can be provided by the District Government to the wider community is government administrative services, such as providing KTPs, Family Cards (KK), and other civil services. However, the need for the sub-district government to improve service reform strategies that refer to the Total Quality Service (TQS) concept, by improving the quality of public service management in the sub-district SKPD can include aspects of human resource capabilities, facilities and infrastructure, procedures implemented, and administrative services provided by service providers (District Government).